Stable knockdown of Drp1 improves retinoic acid-BDNF-induced neuronal differentiation through global transcriptomic changes and results in reduced phosphorylation of ERK1/2 independently of DUSP1 and 6 - Ghani, Marvi; Zohar, Peleg; Ujlaki, Gyula; Tóth, Melinda; Amsalu, Hailemariam; Póliska, Szilárd; Tar, Krisztina (Frontiers in Cell and Developmental Biology, 2024)
This study investigated the effects of Drp1 - a major mitochondrial fission protein - on retinoic acid-BDNF-induced (RA-BDNF) neuronal differentiation and mitochondrial network reorganization. We generated an SH-SY5Y cell line with stably depleted Drp1 (shDrp1). shDrp1 cells exhibited fused mitochondrial ultrastructure with perinuclear clustering. Stable knockdown of Drp1 resulted in the upregulation of genes involved in nervous system development. High content analysis showed improved neurite outgrowth, segmentation, and extremities in differentiated shDrp1 cells. Neuronal differentiation was associated with a significant reduction in ERK1/2 phosphorylation, and ERK1/2 phosphorylation was independent of the dual specificity phosphatases DUSP1/6 in shDrp1 cells. Differentiated control underwent mitochondrial morphology remodeling, whereas differentiated shDrp1 cells retained the highly fused mitochondria and developed long, elongated structures. The shDrp1 cells responded to specific apoptotic stimuli similar to control in vitro, suggesting that Drp1 is not a prerequisite for apoptosis in SH-SY5Y cells. Our results indicate that Drp1 silencing enhances RA-BDNF-induced neuronal differentiation by promoting transcriptional and mitochondrial network changes in undifferentiated cells. Moreover, Drp1 downregulation reduced the formation of toxic mHtt aggregates in vitro. Drp1 may be an attractive target for further investigation in future strategies to combat neurodegenerative diseases.